Biotransformation and stereoselective synthesis of pharmaceutical molecules from linoleic acid - Omar, Muhammad Nor; Muhd Nor, Nor Nazuha; Moynihan, Humphrey; Hamilton, Richard J. (Asian Network for Scientific Information, 2007)
The biotransformation of linoleic acid 1 using immobilised soybean lipoxygenase in a dimethyl sulfoxide (DMSO) containing medium followed by sodium borohydride reduction afforded 13(S)-hydroxy-octadeca-9(Z),11(E)-dienoic acid 13(S)-HODE 2 in 69% yield. After methylation, methyl 13(S)-HODE was subjected to epoxidation using tert-butyl hydroperoxide (TBHP) in the presence of vanadyl acetylacetonate or titanium (IV) isopropoxide with D-(-)- or L-(+)-diisopropyl tartrate. Epoxidation catalysed by titanium (IV) isopropoxide/D-(-)-isopropyl tartarate gave predominantly epoxide 3 (in 75% yield) while treatment of 2 with TBHP in the presence of titanium (IV) isopropoxide and L-(+)-diisopropyl tartrate gave preferentially epoxide 4 in 73% yield. Meanwhile, epoxidation of 2 with TBHP in the presence of vanadyl acetylacetonate gave predominantly epoxide 3 in 72% yield. The fluoro-derivatives 8, 9 and 10 were obtained in high yield when hydroxy-derivative 2, 3 and 4 were converted into their trimethylsilyl derivatives 5, 6 and 7 before treating with diethylaminosulphur trifluoride. Treatment of epoxide 4 with acetamide in dimethyl formamide (DMF) afforded a heterocyclic 2-oxazoline 11 in 73% yield.